Do Research Attitudes Predict Participation? A Quantitative Analysis Using the Research Attitudes Questionnaire - Kouassi, Prince (Universitas Ahmad Dahlan, 2025)
This study aimed to examine whether positive attitudes toward research predict actual participation behaviour in online research settings. The Research Attitudes Questionnaire (RAQ) was used to assess individuals’ beliefs about research, while verified participation records from the Prolific platform served as the behavioural outcome measure.A total of 215 participants completed the seven-item RAQ and provided consent for their verified participation data to be accessed through the Prolific platform. A simple linear regression analysis was conducted, with RAQ scores as the predictor variable and the total number of completed studies as the outcome variable. Participants reported generally favourable attitudes toward research; however, RAQ scores did not significantly predict verified participation behaviour (β = .071, p = .28). Attitudes accounted for only a small proportion of the variance in participation (R² = .005), suggesting limited predictive power. These findings highlight a disconnect between attitudinal endorsement and actual behaviour, consistent with the intention-behaviour gap described by Ajzen’s Theory of Planned Behaviour. The results underscore the limitations of using attitudinal measures alone to predict research engagement and suggest that integrative models incorporating individual, contextual, and structural factors are needed to improve participation rates, particularly in online contexts.